ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN UPAYA PENCEGAHAN ANEMIA SAAT MENSTRUASI PADA REMAJA PUTRI DI SMA NEGERI KABUPATEN SOPPENG - Sri Rezkiani Kas; Musyahidah Mustakim (Asosiasi Dosen Muda Indonesia, 2022)
Many young women do not know and realize that they have anemia, even though they know that they have anemia, they still think that anemia is a trivial problem. Young women are prone to anemia. The existence of a monthly menstrual cycle is one of the factors that cause young women to be prone to anemia, moreover, driven by their lack of knowledge about anemia. This study aims to analyze the factors associated with the prevention of anemia during menstruation in adolescent girls at Public High School Soppeng Regency. The type of research used is descriptive correlational research with a cross sectional approach. Based on the results of the analysis showed that there was a relationship between knowledge (0.000) and efforts to prevent anemia during menstruation. Researchers suggest for health workers to increase counseling and counseling as well as guidance for young women to prevent anemia.